Impact of the Strategy for Risk Management in Schools of Santo Domingo de Heredia, Costa Rica - Fernández Arce, Mario (2021)
The Strategy for Disaster Risk Management in the Education Sector of the Republic of Costa Rica has abundant goals and results to improve risk management in educational communities, but its impact on the Santo Domingo school sector has not been evaluated yet. This plan was created in 2014 but there is still no measurement of its influence on the training of teachers from the studied area. The objective of this work is to inform about the role of the approach in risk management in 8 schools in Santo Domingo. The qualitative and basic research focused on the results proposed by the plan and was carried out between 2018 and 2019. To obtain the required information, the research group asked data to the person who teaches risk management in the selected schools as well as the coordinator of the risk management committee. This required two instruments (questionnaires) with short-answer questions alluding to the products of the strategy expected in 2020. The research group found that some teachers have been trained, but those trained are few with respect to the proposed goals and the courses carried out are more on emergency care than on risk prevention. The results indicate that the strategy is being used, but its influence is little in the management of risks in the schools of Santo Domingo. Such conclusion implies that efforts must be increased so that the Strategy generates the expected results.